2008
DOI: 10.1007/s10163-008-0200-x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of phenols in leachates from municipal solid waste landfill sites in Japan

Abstract: The concentrations of 41 phenols in leachates from 38 municipal solid waste (MSW) landfi ll sites in Japan were measured. The main phenols detected in leachates were phenol, three cresols, 4-tert-butylphenol, 4-tertoctylphenol, 4-nonylphenol, bisphenol A, and some chlorophenols. The concentration levels of phenols were affected by the pH values of the leachates and the different types of landfi ll waste. The origins of phenol and p-cresol were considered to be incineration residues, and the major origin of 4-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 12 publications
(32 reference statements)
5
33
2
Order By: Relevance
“…The presence of BPA in MAC effluent was, however, highly variable with about 25% of all wastewater samples taken at MAC having BPA concentrations below detection limits (approximately 1,100 ng L −1 ). Exploratory sampling conducted in January 2016 of the regional landfill's leachate, which is periodically released into the MAC sewage system, found a BPA concentration of 638,000 ng L −1 , high for municipal landfill leachate (Kurata et al, 2008). Given the relatively large volumes and periodic release of the landfill leachate into the MAC sewage system, it is considered probable that this is the source of the periodically high BPA concentrations measured at MAC.…”
Section: Post-2014 Quarterly Wastewater Samplingmentioning
confidence: 99%
“…The presence of BPA in MAC effluent was, however, highly variable with about 25% of all wastewater samples taken at MAC having BPA concentrations below detection limits (approximately 1,100 ng L −1 ). Exploratory sampling conducted in January 2016 of the regional landfill's leachate, which is periodically released into the MAC sewage system, found a BPA concentration of 638,000 ng L −1 , high for municipal landfill leachate (Kurata et al, 2008). Given the relatively large volumes and periodic release of the landfill leachate into the MAC sewage system, it is considered probable that this is the source of the periodically high BPA concentrations measured at MAC.…”
Section: Post-2014 Quarterly Wastewater Samplingmentioning
confidence: 99%
“…Particularly, the disposal of incineration residues including solidified fly ash and the co-disposal of incombustibles and solidified fly ash can increase the opportunity of environmental pollution. A series of traditional wastewater treatment processes can remove phenol, 4-nonylphenol, and bisphenol to an acceptable level (Kurata et al, 2008). Because of its negative effects on public health and ecosystems, phenol and its related compounds have been given high priority in governmental regulations in many countries (Ahn et al, 2008;Kurata et al, 2008;Kujawski et al, 2004;Tziotzios et al, 2007;Xiao et al, 2006).…”
Section: Leachate Characterizationmentioning
confidence: 99%
“…A series of traditional wastewater treatment processes can remove phenol, 4-nonylphenol, and bisphenol to an acceptable level (Kurata et al, 2008). Because of its negative effects on public health and ecosystems, phenol and its related compounds have been given high priority in governmental regulations in many countries (Ahn et al, 2008;Kurata et al, 2008;Kujawski et al, 2004;Tziotzios et al, 2007;Xiao et al, 2006). In this research, 4-aminoantipyrine method was used to measure phenols by determining all ortho-substituted and meta-substituted phenols or napthols, but not para-substituted phenols.…”
Section: Leachate Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Horowitz et al [3] reported that in anoxic sediments, m-and p-cresol isomers showed the maximum degradation, while o-cresol resisted degradation. Kurata et al [4] investigated occurrence of phenolic compounds in leachates from 38 Municipal Solid Waste landfills in Japan and found that most of the landfill leachates contained 3.7 μg/L of o-cresol. Most health exposures of o-cresol observed in people include irritation and burning of skin, eyes, mouth, and throat, abdominal pain and vomiting, heart damage, anemia, liver and kidney damage facial paralysis, coma, and death [5].…”
Section: Introductionmentioning
confidence: 99%